2019
DOI: 10.1002/ptr.6424
|View full text |Cite
|
Sign up to set email alerts
|

The effects of black seed supplementation on cardiovascular risk factors in patients with nonalcoholic fatty liver disease: A randomized, double‐blind, placebo‐controlled clinical trial

Abstract: Nonalcoholic fatty liver disease (NAFLD) is highly related to cardiovascular disorders risk factors. This study aimed to evaluate the effects of black seed (Nigella sativa) supplementation on cardiovascular disorders risk factors in patients with NAFLD. This randomized, double‐blind, placebo‐controlled clinical trial was conducted on 50 patients with NAFLD. Participants were assigned to receive a lifestyle modification plus 2 g/day of either N. sativa or placebo for 12 weeks. Compared with the placebo, N. sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 37 publications
2
31
0
1
Order By: Relevance
“…Weight reduction is considered a way to alleviate the CVD risk factors directly and indirectly by affecting WC. In accordance with the results, Darand et al (2019) demonstrated that 2 g of NS powder resulted in a significant reduction in weight, BMI, and HC after 12 weeks of supplementation. Also, Mahdavi, Namazi, Alizadeh, and Farajnia (2015) showed that daily consumption of 3 g NS oil for 8 weeks in obese women reduced weight, WC, and WHR significantly.…”
Section: Effects Of Ns On Anthropometric Parameterssupporting
confidence: 90%
“…Weight reduction is considered a way to alleviate the CVD risk factors directly and indirectly by affecting WC. In accordance with the results, Darand et al (2019) demonstrated that 2 g of NS powder resulted in a significant reduction in weight, BMI, and HC after 12 weeks of supplementation. Also, Mahdavi, Namazi, Alizadeh, and Farajnia (2015) showed that daily consumption of 3 g NS oil for 8 weeks in obese women reduced weight, WC, and WHR significantly.…”
Section: Effects Of Ns On Anthropometric Parameterssupporting
confidence: 90%
“…Khonche et al (2019) showed that consumption of 2.5 mL N. sativa Seed Oil, 1.25 mL honey and 1.25 mL water as mixture after 3 months altered triglyceride, LDL) and HDL in patients with nonalcoholic fatty liver disease. Darand, Darabi, Yari, Hedayati, et al (2019) showed in patients with nonalcoholic fatty liver disease, consumption of 500 mg/day milled edible N. sativa after 12 weeks, did not alter TG, HDL‐C, total cholesterol, and LDL‐C concentrations. Elfouly et al (2019) observed that supplementation of N. sativa seed extracts 1 g/day along with atorvastatin drug did not alter any of the lipid profiles in adult patients with dyslipidemia after 6 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…Bilal et al (2009) reported a significant fall in fasting glucose levels and rise in insulin for patients with type 2 diabetes after consumption of N. sativa seeds 0.7 g daily for 40 days. The trial by Darand, Darabi, Yari, Hedayati, et al (2019) showed a clear glycemic effects on fasting glucose, insulin levels, and HOMA index following N. sativa supplementation at a daily dose of 500 mg pending 12 weeks in patients with nonalcoholic fatty liver disease even after adjusting known confounders. In another study by Rashidmayvan et al (2019) in patients with nonalcoholic fatty liver disease, significant reduction in fasting glucose level was observed after 12 weeks of taking 1 g of N. sativa oil once a day, with no beneficial effects on serum levels of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Black cumin seed has been tested in recent randomized controlled trials (RCTs) for treatment of nonalcoholic fatty liver disease (NAFLD). A double‐blinded, placebo‐controlled RCT evaluated black cumin seed consumption in adults with NAFLD (Darand et al., 2019). These participants consumed 2 g of ground black cumin seed daily ( n = 21) or a placebo ( n = 22) for 12 weeks.…”
Section: Health Benefits Of Specialty Seedsmentioning
confidence: 99%